10% Higher Rowing Power Outputs After Flexion-Extension-Cycle Compared to an Isolated Concentric Contraction in Sub-Elite Rowers - Held, Steffen; Siebert, Tobias; Donath, Lars (Frontiers in Physiology, 2020)
The resulting muscular performance is considered notably higher during a stretch-shortening-cycle (SSC) compared to an isolated concentric contraction. Thus, the present study examined the occurrence and magnitude of rowing performance enhancement after a flexion-extension cycle (FEC) of the legs compared to both concentric contractions only and isometric pre-contraction. Therefore, 31 sub-elite male rowers (age: 25 ± 6 years, height: 1.90 ± 0.02 m, weight: 91 ± 10 kg, weekly training volume: 11.4 ± 5.3 h/week, rowing experience: 7.1 ± 2.7 years) randomly completed a) isolated concentric rowing-strokes (DRIVE), b) single FEC type rowing-strokes (SLIDE-DRIVE) and c) rowing-strokes with an isometric pre-contraction (ISO-DRIVE). The resulting rowing-power (Prow), leg-power (Pleg) and work-per-stroke (WPS) were recorded using motion-capturing, force- and rotation-sensors. Comparison of DRIVE and SLIDE-DRIVE revealed significantly (p < .05) higher Prow (+11.8 ± 14.0 %), Pleg (+19.6 ± 26.7 %) and WPS (+9.9 ± 10.5 %) during SLIDE-DRIVE. Compared to ISO-DRIVE, Pleg (+9.8 ± 26.6 %), and WPS (+6.1 ± 6.7 %) are again significantly (p < .05) higher for SLIDE-DRIVE. In conclusion, notably higher work- and power-outputs (compared to an isolated concentric contraction) during FEC rowing refer to an underlying SSC. Future ultrasound studies should elucidate whether a real SSC on muscle tendon unit level account for these performance enhancements.